Hovering on Screen: The WOW-Affect and Fan Communities of Affective Spectatorship on So You Think You Can Dance - Elena Benthaus (The International Journal of Screendance, 2015)
In this article I argue that the television dance franchise So You Think You Can Dance fosters and encourages what I call affective viewing practices and communities of affective spectatorship, which are specifically related to the "WOW-affect" created by its affective bodies. I use the term 'affect' to indicate the relationship between screens, athletic/virtuosic bodies, sound, and movement as one of excessive stimulation, resulting in intensities, or affects, which are circulated between screens and bodies as particular moments of suspense. In this sense, affect can be located in the gap between the impact of a stimulation on the skin-surface and a more coherent, cognitive response to this stimulation. The WOW as an utterance in relation to the athletic/virtuosic screen bodies and their affective impact gives voice and physical expression to the excess of intensities as a not-yet-cognitive suspended response. The notion of the WOW-affect, combining the utterance with a specific affective impact, is closely linked to the vaudeville show aesthetics of using an intensely spectacular movement series at the end of a routine to 'stop the show' by stunning the audience and suspending their reaction for a brief moment in time. Hence, the WOW-affect is a particular reaction to the experience of movement.
Keywords: popular screen dance; affective bodies; affective spectatorship and community